Title to Land in Nigeria: Past and Present - Oretuyi, Solomon Akinboye (2012)
In this Inaugural Lecture I shall discuss title to land in Nigeria before and after March 29, 1978. One characteristic of the land holding before 1978 was the dual system of land tenure. Under the dual system of tenure, some titles were held under English law while the majority of titles were under customary law. Dualism in tenurial system was a product of the introduction of the English legal system in Nigeria, Originally, all lands were held under customary tenure but with the introduction of the English legal system, lands held under customary tenure were converted to English titles by the use of English conveyancing formalities. It is pertinent to point out that the dual system of land, tenure was peculiar to Southern Nigeria. In Northern Nigeria, all lands were brought under the control of the government by the Land Native Rights Proclamation of 1910. This Proclamation was repealed and re-enacted as Land and Native Right Ordinance 1916. This was subsequently replace by Land Tenure Law 1962 which continues to apply subject to such modification as will bring it into conformity with the Act or its general intendment.